Urban Anthropology: An Overview of the Discipline and Scope - Bhandari, Amrit Kumar (Himalayan Journal of Sociology and Anthropology, 2011)
Based on the review of some selected literatures, this article attempts to explain Urban Anthropology as an emerging sub-ield within Sociocultural Anthropology. In this process, it reviews the history of the subield in short and elaborates its ield of scope in the modern rapidly urbanizing world. Deinitely, the process of urbanization has also been given adequate emphasis by highlighting its concept and nature. Even the status of urbanization in Nepal has also been given place in brief. The article towards the latter part explains about the prospects of Urban Anthropology in Nepal. DOI: http://dx.doi.org/10.3126/hjsa.v4i0.4664 Himalayan Journal of Sociology and Anthropology Vol.IV (2010) 1-14